A dimensão investigativa no exercício profissional do Assistente Social : limites e possibilidades - Medeiros, Jaqueline Dayane da Silva (2017)
This dissertation proposes an analysis of the investigative dimension in the professional exercise Social Worker, linked to the Health Polícy of the county of Cuiaba-MT. Had reference in authors as Guerra (2009); Iamamoto (2015); Baptista (2001); Battini (2009) e Bourguignon (2008), who understand the investigative dimension in the professional exercise as going to the dimension of the “new” in the profession, which puts the capacity to assign the intervention more consistent, propositive, from the critical investigative capacity of reality analysis. This relationship impresses for the professional exercise the quality and the practical commitment both in the way of dealing with the expressions of the social question and the intellectual dimension of the profession. In order to reach the proposed objectives, we used descriptive research of a qualitative nature, using as data collection instruments the interview technique in a free way, appropriate for the collection of “personal testimonies” (QUEIROZ, 1991). The interview was conducted with 06 (six) Social Assistants linked to the Health Policy of the municipality of Cuiabá-MT. The research reveals the lack of knowledge by the professionals of the relation between the investigative and interventional dimensions; such as the fragility in the identification and apprehension of the private assignments of the Social Worker in the spaces of action, which makes it difficult to overcome immediate, emergency and repetitive practices. In this way the research demonstrates the need to advance in continuing formation actions, that favor knowledge from the systematization of practical actions and planning, in articulation with the theoretical-methodological, ethicalpolitical and technical-operative dimensions in which the dimension the investigation. It is to apprehend the investigative dimension as a subsidy for the professional exercise to understand the meaning of the demands placed on the intervention, and thus to enable qualified and investigative responses qualified in accordance with the Social Service Political Ethics Project.